First Day - McKamy, Sheila (Journal of the American Academy of Special Education Professionals, 2009)
She looks really nice as she stands at the door,I slump forward to meet her, staring at the floor. What will she see when she looks at me?Will she see me?The teenager standing in front of her, hoping for a fresh start, a new year.